2011
DOI: 10.1111/j.1365-2729.2011.00417.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in students' use of optional learning resources

Abstract: We investigated ways in which undergraduates use optional learning resources in a typical blended learning environment. Specifically, we recorded how often students attended live faceto-face lectures, accessed online recorded lectures, and visited a mathematics learning support centre during a multivariate calculus course. Four distinct study strategies emerged, but surprisingly none involved making heavy use of more than one resource. In contrast with some earlier research, the general strategy a student adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 24 publications
(35 reference statements)
5
55
2
1
Order By: Relevance
“…They noticed a gender difference in attendance rates, and suggested that women have "far higher" attendance (p. 43). This suggestion is consistent with Inglis, Palipana, Trenholm, and Ward's (2011) study of a first year calculus module, in which women mathematics students were found to attend significantly more lectures than men. 1 Rodd and Bartholomew also suggested that women participate differently in the classroom.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…They noticed a gender difference in attendance rates, and suggested that women have "far higher" attendance (p. 43). This suggestion is consistent with Inglis, Palipana, Trenholm, and Ward's (2011) study of a first year calculus module, in which women mathematics students were found to attend significantly more lectures than men. 1 Rodd and Bartholomew also suggested that women participate differently in the classroom.…”
Section: Introductionsupporting
confidence: 78%
“…Solomon et al (2011) (Barrett & Lally 1999), whereas others have found the reverse (Jackson, Ervin, Gardner, & Schmitt 2001). In a calculus course, Inglis, Palipana, Trenholm, and Ward (2011) found that male undergraduates more often watched recordings of lectures online than females. However, they noted that the majority of the women in their sample were studying mathematics, whereas most men were studying engineering, so the difference may have been due to discipline rather than gender.…”
Section: Introductionmentioning
confidence: 99%
“…Some research suggests that more frequent access to recorded lectures leads to an increase in positive results and learning behaviours (Phillips et al, 2011;Traphagan et al, 2010). Inglis, Palipana, Trenholm, and Ward (2011), on the other hand, found that "students who often accessed online lectures had lower attainment than those who often attended live lectures or the support centre" (p. 490). Owston et al (2011) reviewed data from 860 undergraduate students and found the same was true: "[S]tudents who accessed the recordings once per month or less often achieved significantly higher grades than those who accessed them 4 to 6 times per week or more often."…”
Section: Impact Of Lecture Capture On Academic Performancementioning
confidence: 99%
“…Nevertheless, we attempted to control for key factors which might covary with PAL attendance and mathematical achievement. Specifically, earlier research has demonstrated that higher lecture attendance is associated with higher achievement in undergraduate mathematics [39].…”
Section: Session Attendance and Achievementmentioning
confidence: 99%